Further Spread of blaNDM-5 in Enterobacteriaceae via IncX3 Plasmids in Shanghai, China - Zhang, Fangfang; Xie, Lianyan; Wang, Xiaoli; Han, Lizhong; Guo, Xiaokui; Ni, Yuxing; Qu, Hongping; Sun, Jingyong (Frontiers in Microbiology, 2016)
One hundred and two carbapenem-resistant Enterobacteriaceae (CRE) strains were isolated in a teaching hospital in Shanghai, China from 2012 to 2015. In a follow-up study, 4 New Delhi metallo-β-lactamase-5 (NDM-5)-producing strains were identified after screening these CRE strains, including 1 Klebsiella pneumoniae strain (RJ01), 1 Proteus mirabilis strain (RJ02), and 2 Escherichia coli strains (RJ03 and RJ04). All K. pneumoniae and E. coli isolates were resistant to carbapenems, third-generation cephalosporins, and piperacillin-tazobactam, but were susceptible to amikacin. No epidemiological links for either E. coli isolate were found by multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE). However, MLST revealed a novel sequence type, ST2250, of the K. pneumoniae RJ01 strain. Inc types and sizes of blaNDM-5-carrying plasmids differed among the 4 isolates, although in P. mirabilis RJ02 and E. coli RJ03, blaNDM-5 was carried by conjugative IncX3 plasmids of nearly the same size (~40 kb). Investigation of the genetic background of sequences flanking the blaNDM-5 gene showed that all 4 isolates shared the same genetic content (IS3000-ΔISAba125-IS5-blaNDM-5-ble-trpF-dsbC-IS26-ΔumuD), which was identical to that of the pNDM_MGR194 plasmid circulating in India. This is the first identification of blaNDM-5 in P. mirabilis, which suggests its further spread to Enterobacteriaceae, and indicates that IncX3 plasmids may play an important role in potentiating the spread of blaNDM.